(untitled) (Research, Society and Development, 2025)
This investigation aims to present a study on the integrality of palliative care and the ethical, spiritual, and human role of nursing, conducted through an experience report based on hospital practice. Palliative care is an approach aimed at providing quality of life, pain relief, and physical, psychological, social, and spiritual comfort to patients and their families facing life-threatening illnesses. This report describes experiences in a Federal Hospital in Rio de Janeiro during a multiprofessional residency in Medical and Surgical Nursing. The qualitative, descriptive methodology was based on practical experience and the theoretical frameworks of Cicely Saunders and Katharine Kolcaba. The results show that nursing serves as an essential link between patients, families, and the healthcare team, promoting dignity, spirituality, and emotional support. It is concluded that palliative care goes beyond the clinical management of pain, integrating ethical, emotional, and spiritual dimensions.